1975
DOI: 10.1093/oxfordjournals.jbchem.a130995
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Multi-Branched Dextrins Produced by Saccharifying α-Amylase from Starch

Abstract: From the digest of beta-limit dextrin (prepared from glutinous rice starch) with saccharifying alpha-amylase of Bacillus subtilis [EC 3.2.1.1] (BSA), two extensibely branched dextrins consisting of nine (No. 6, Fig. 1) and ten (No 7, Fig.1) glucose units were isolated by paper chromatography. Structural analysis using various enzymes revealed that No. 6 and No. 7 were both mixtures of four triply branched dextrins. They had structures which were built up with 63-alpha-glucosylmaltotriose and/or 62-alpha-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In sample III, dextrins corresponding to the branched blocks of group 3 at DP 10-15 preponderated. At DP [16][17][18][19], which corresponded to group 4, the chromatograms possessed double or triple peaks at each DP value, suggesting a manifold of multiply branched dextrins. As the elution time simultaneously decreased with increasing branches, exact assignments of the DPs for these peaks were difficult to make.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In sample III, dextrins corresponding to the branched blocks of group 3 at DP 10-15 preponderated. At DP [16][17][18][19], which corresponded to group 4, the chromatograms possessed double or triple peaks at each DP value, suggesting a manifold of multiply branched dextrins. As the elution time simultaneously decreased with increasing branches, exact assignments of the DPs for these peaks were difficult to make.…”
Section: Resultsmentioning
confidence: 99%
“…e Average inter-block degree of polymerization. f Branched building blocks of group 2 (DP 5-9), 3 (10-15), 4 (16)(17)(18)(19), and 5 (≥20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They described the structure of singly and multiply branched limit dextrins from waxy rice in great detail and found that, by far, the most prominent dextrins are only singly branched. In LDs with three or more chains, they found that the branches are separated by one or two glucose residues (i.e., ICL is 1 or 2) and that branches never appear next to each other in amylopectin (Umeki and Yamamoto 1975a).…”
Section: Building Blocksmentioning
confidence: 99%